The Higgs boson mass in minimal technicolor models - Doff, A.; Natale, A. A. [UNESP]; Nielsen, M.; Navarra, F. S.; Bracco, M. E. (Amer Inst Physics, 2010)
Recently a Minimal and an Ultraminimal Technicolor models were proposed where the presence of TC fermions in other representations than the fundamental one led to viable models without conflict with the known value for the measured S parameter. In this work we apply the results of [5] to compute the masses of the Higgs boson in the case of the Minimal and Ultraminimal Technicolor models.
Keywords: Technicolor models; Composite particle models